Mathematics
mzlayla
28

If given f(x) = x + 4 and g(x) = –2x^2 + 3x – 1, what is (f – g)(x)? A.(f – g)(x) = –2x^2 + 4x – 3 B.(f – g)(x) = –2x^2 – 2x + 5 C.(f – g)(x) = 2x^2 + 2x + 5 D.(f – g)(x) = 2x^2 – 2x + 5 Please select the best answer from the choices provided

+2
(2) Answers
ButterKing

(f-g)(x)=f(x)-g(x) (f-g)(x)=x+4+2x^2-3x+1 (f-g)(x)=2x^2-2x+5

ashleyam2128

f-g = x+4 - (-2x^2+3x-1) = 2x^2 -2x +5 ---> (B) is the answer Join same degree terms and pay attention to minus signs. That's all!

Add answer